Effects of Prospective Audit and Feedback in Patients with Extended-Spectrum β-Lactamase-Producing Escherichia coli Bacteremia - Yota Yamada; Motoyasu Miyazaki; Hisako Kushima; Hitomi Hirata; Arata Ogawa; Yukie Komiya; Chika Hagiwara; Akio Nakashima; Hiroshi Ishii; Osamu Imakyure (Microorganisms)
Antimicrobial stewardship (AS) Guidelines by the Infectious Diseases Society of America recommend employing prospective audit and feedback (PAF) as an effective intervention in AS programs. Since July 2022, our hospital has implemented PAF for all patients with positive blood cultures, including those with extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (EC) bacteremia. Our study examined the effect of PAF on clinical outcomes in patients with ESBL-EC bacteremia. We enrolled 62 patients diagnosed with ESBL-EC via blood culture who were undergoing antibiotic treatment. The patients were divided into the pre-PAF and post-PAF implementation groups. The rate of antibiotic de-escalation from broad-spectrum antibiotics to narrow-spectrum cefmetazole was significantly higher in the post-PAF group than in the pre-PAF group (80.7% vs. 32.4%, p = 0.0003). The treatment failure rate in the pre-PAF group was higher than that in the post-PAF group (38.7% vs. 12.9%, p = 0.04). The results of this study indicate that the implementation of PAF is advantageous not only in terms of process indicators but also in improved clinical outcomes, including reduced treatment failure rates. We hope that this study will encourage the implementation of PAF in more facilities to instigate a collective effort to reduce the incidence of antimicrobial resistance.